The Themes of Entrepreneurship Discourse: A Data Analytics Approach - Philip T. Roundy; Arben Asllani (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Scholars are devoting heightened attention to the language of entrepreneurship and to its influence on the cognition, behaviors, and outcomes of entrepreneurs and their stakeholders. However, the primary themes that constitute entrepreneurs’ language are unexamined. In this partially-inductive study, we identify the most common themes in entrepreneurship discourse and explore how they have changed over time. To map the themes in entrepreneurs’ language, we use data analytic techniques coupled with text mining algorithms to analyze a longitudinal corpus of entrepreneurial discourse. Our findings reveal five dominant and recurring themes in entrepreneurship discourse – marketing activities, technology-oriented entrepreneurship, digital entrepreneurship, professional investment, and new venture entrepreneurship – and illustrate how these themes are evolving. By examining the key themes in the discourse of entrepreneurs and charting their transformation over time, our study makes theoretical and methodological contributions to entrepreneurship research. We identify the areas where the academic literature seems to be lagging practitioner discussions and suggest that scholars should evaluate research for how closely topics are calibrated with the main themes in the discourse of entrepreneurs. Our findings also produce practical implications for entrepreneurs by identifying the main themes receiving attention, which allows entrepreneurs to evaluate if the topics that comprise their day-to-day discourse align with the themes emphasized in the larger body of entrepreneurship discourse.